An Institutional Analysis of Research and Development Expenditure - Epictetus Patalinghug (Philippine Institute for Development Studies (PIDS), 1999)
It is the government's role in the science and technology sector to foster cooperation between government, academe and industries; establish a competitive science research funding mechanism; promote the development of science and technology manpower; and establish a system to monitor, assess and forecast technology. To strengthen science and technology education at the elementary and secondary levels, however, requires an upgrading of laboratory facilities and equipment and hiring of qualified teachers. This paper enumerates measures to address the incentive problem in the science and technology sector, suggests ways to enhance research and development delivery system; and offers solutions to improve the science and technology coordination mechanism.
Keywords: 330; science and technology; competition